AB0009 PADI4 Gene Polymorphism as A Predictor of Response To Methotrexate in Patients with Juvenile Idiopathic Arthritis. (15th July 2016) - Nazarova, L.S.; Danilko, K.V.; Malievsky, V.A.; Viktorova, T.V.
Abstract : Background: Methotrexate (MTX) is the most widely used disease-modifying anti-rheumatic drug in the treatment of juvenile idiopathic arthritis (JIA); however, there is a variation in the clinical response to MTX among the patients [1]. Previous studies have shown conflicting results regarding predictors of the response to MTX. No unequivocal predictive SNP has been found yet, because many were assessed in only one study, or were predictive in one study and showed no effect in others [2]. Objectives: The aim of the study was to assess whether the PADI4 rs2240336 gene polymorphism is a predictor of the disease severity and the response to MTX in patients with JIA from Bashkortostan, Russia. Methods: 283 patients with JIA were genotyped for the PADI4 rs2240336 gene polymorphism using real-time PCR. The statistical analysis was performed using two-tailed Fisher's exact test, odds ratio, 95% confidence interval and logistic regression in Microsoft Excel, WinPepi v.11.44, R v.3.2.0, SNPStats programs. The disease course was assessed as more severe if the MTX therapy was required. The response to MTX was considered as good if clinical remission on medication (Wallace) was achieved, otherwise – as insufficient. An addition of a biological agent to the MTX therapy was also assessed as a marker of an insufficient response. Results: The requirement of the MTX treatment and its absence was noted at 261 (92.3%) and 22 (7.8%) children with JIA respectively, and the distribution of the genotypes and alleles of the PADI4 rs2240336 gene polymorphism were similar in both groups (p=0.982). At the same time the frequency of the genotype AG was significantly higher (59.8% vs. 35.5%, p=0.0029, OR=2.71, 95% CI 1.41–4.94), and the frequency of the genotype GG was significantly lower (23.8% vs. 45.2%, p=0.0041, OR=0.38, 95% CI 0.20–0.73) in patients, who received MTX and not achieved clinical remission on medication (n=122) than in those who achieved (n=62). The best model of inheritance was overdominant, where the genotype AG marked an insufficient response to MTX (AG vs. GG + AA, p=0.0017, OR=2.71, 95% CI 1.44–5.11). The association with an insufficient response to MTX was also observed under the dominant (AG + AA vs. GG, p=0.0034, OR=2.64, 95% CI 1.38–5.06) and codominant (AG vs. GG, p=0.0041, OR=3.20, 95% CI 1.58–6.48) models of inheritance. Moreover, the genotype AG frequency was significantly elevated in patients who required an addition of a biological agent to the MTX therapy (n=73) (p=0.012, OR=2.097, 95% CI 1.20–3.66) and the overdominant model of inheritance also proved the best (p=0.0088, OR=2.10, 95% CI 1.20–3.68). Conclusions: Thus, in this study we revealed that the genotype AG of the PADI4 rs2240336 gene polymorphism was a marker of increased risk of an insufficient response to MTX in children with JIA from Bashkortostan, Russia. If this finding will be confirmed in other studies, it can be potentially used for the early prediction of the response to MTX in patients with JIA. References: Albarouni M, Becker I, Horneff G. Predictors of response to methotrexate in juvenile idiopathic arthritis. Pediatric Rheumatology Online Journal. 2014;12:35. Van Dijkhuizen EP, Wulffraat NM. Prediction of methotrexate efficacy and adverse events in patients with juvenile idiopathic arthritis: a systematic literature review. Pediatric Rheumatology Online Journal. 2014;12:51. Disclosure of Interest: None declared